Home range and activity pattems of Conepatus semistriatus (Carnivora, Mephitidae) in Emas National Park, Brazil - Nunes Cavalcanti, Gitana (2014)
The home range, habitat use, and distance from water sources were estimated for Basiliscus plumifrons in an agricultural matrix in Costa Rica. Using radio telemetry, four females and four males were studied from July-September (2004) in a cocoa (Theobroma cacao) farm embedded in landscape dominated by banana and pineapple plantations. Females occupied a home range that averaged 1877 ± 1052 m 2 (n = 4); male home ranges were similar, averaging 1740 ± 1288 m 2 (n = 4; t-test = -0.12, P = 0.90). Cacao with a limited shade canopy was the predominant habitat available and used most frequently when compared to other habitats (χ © 2007 Brill Academic Publishers. 2 = 116.67; P < 0.0001). Basiliscus plumifrons remained close to water although individuals occasionally traveled up to 80 m from water. However, both males (24.30 ± 1.93 m, n = 133) and females (26.82 ± 1.97 m, n = 128) maintained similar average distances from water resources (Kruskal-Wallis, H = 1.57, P = 0.20). Agroforestry systems connected to patches of riparian forest probably play an important role in the ecology and conservation of B. plumifrons.